Advanced nitrogen removal in a fixed-bed anaerobic ammonia oxidation reactor following an anoxic/oxic reactor: Nitrogen removal contributions and mechanisms. (January 2021) - Sui, Qianwen; Di, Fei; Zhang, Junya; Gong, Hui; Jiang, Li'an; Wei, Yuansong; Liu, Jie; Lin, Jia
Graphic abstract: Highlights: Anammox in a UFBR served as tertiary process for nitrogen polishing. UFBR contributed to 12.7–23.4% on TN removal, and 17.2–20.0% on NH4 + -N removal. 90% of TN was removed through the combination of PN and PD with anammox in UFBR. Cooperation of AOA, AOB and AnAOB for nitrogen removal was achieved in the UFBR. AOA ( Nitrosopumilus ) in inner of biofilm anaerobically produced NO2 − -N for anammox. Abstract: This study demonstrated the feasibility of anaerobic ammonia oxidation (anammox) served as tertiary nitrogen removal process. An upflow fixed-bed reactor (UFBR) pre-inoculated with anammox bacteria (AnAOB) followed an anoxic/oxic (A/O) reactor treating magnetic-coagulation pretreated municipal wastewater. When bypassing 15% of influent into UFBR, UFBR removed 5.37 mg-TN/L contributing to 23.4% on total TN removal, in which the combination of partial nitritation and partial denitrification with anammox was main nitrogen removal pathway. Relatively low concentrations of NH4 + -N and anaerobic environment promoted the growth of ammonia oxidizing archaea (AOA) in the inner-layer of biofilm in UFBR. The cooperation of AOA and ammonia-oxidizing bacteria (AOB) with AnAOB was achieved, with AOA, AOB, and AnAOB abundances of 0.01–0.32%, 0.25–0.44%, and 0.77–2.18% on the biofilm, respectively. Metagenomic analysis found that although AOB was the main NH4 + -N oxidizer, archaeal amo gene on biofilm increased threefold during 90 days' treatment.